2017
DOI: 10.1111/apps.12111
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Flexibility at Work and Employees' Proactive Work Behaviour: Cross‐Level Moderating Role of Leader Need for Structure

Abstract: How to promote employees to be proactive behaviourally is a significant issue in the literature because it would benefit organisations in several ways. Drawing on the acceptance and commitment model, we proposed a new antecedent, psychological flexibility that might contribute to employees proactive work behaviour. Furthermore, we investigated how the contextual role of supervisor need for structure exhibits a cross-level moderating effect on the relationship between employee psychological flexibility at work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This is because the professional’s attention and energy are not directed at controlling negative internal experiences, and therefore, they are more sensitive to the information provided by the work environment to initiate goal-directed behaviors [ 61 ]. In addition, coping based on psychological acceptance is less resource-intensive than coping based on emotional control [ 62 ]. Thus, psychological flexibility has also been shown to be associated with increased performance and productivity [ 60 ] increased vitality [ 63 ] and decreased levels of emotional burnout [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because the professional’s attention and energy are not directed at controlling negative internal experiences, and therefore, they are more sensitive to the information provided by the work environment to initiate goal-directed behaviors [ 61 ]. In addition, coping based on psychological acceptance is less resource-intensive than coping based on emotional control [ 62 ]. Thus, psychological flexibility has also been shown to be associated with increased performance and productivity [ 60 ] increased vitality [ 63 ] and decreased levels of emotional burnout [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“… 53 In addition, team size was also controlled for because prior research suggested that size might influence the level of proactive behavior on the part of employees. 54 …”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, researchers have observed a positive relationship between teacher emotion and proactive behaviour toward change (Hargreaves, 2005;Saunders, 2013). However, to date, only a handful of studies have been performed to examine how personal cognitive and emotional factors are related to proactive behaviour (Kuo et al, 2018;Montani et al, 2014;Salanova and Schaufeli, 2008). Moreover, there has been little exploration of how individual workplace learning activity contributes to proactive behaviour.…”
Section: Proactivity and Proactive Motivationmentioning
confidence: 99%